Penerapan Program Hafalan Al-Qur’an dalam Meningkatkan Akhlakul Karimah Santri PPTQ Al-Hafidz Jombang - Veri, Achmad Riyan; Kholid, Abdul (JoEMS (Journal of Education and Management Studies), 2023)
The aim of this research is to determine the application of the Al-Qur'an memorization program in improving the morals of students at the Tahfidzul Qur’an Al-Hafidz Trawasan Sumobito Jombang Islamic boarding school. This research uses a qualitative approach with the type of field research, so that researchers are directly involved during the research process. The data collection technique was carried out using triangulation (a combination of descriptive data analysis and research results that emphasized the meaning of akhlakul karimah). With the implementation of an Al-Qur'an memorization program in which there are rules, such as: staying away from madzmumah (morals). despicable ones), etiquette when memorizing the Qur’an and Islamic boarding school rules and regulations that must be obeyed, so that it will direct a student to have an akhlakul karimah attitude that is in accordance with the contents of the Qur’an.